The Information Culture Level of Uzbekistan Students at Islamic Studies College - Anvarov, A.A. (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2024)
This article describes information culture in the modern period and its distinctive characteristics. Researchers have looked into the social elements that lead students at a special Islamic educational college to lack a critical approach to selecting the necessary information. The author also presented a number of suggestions and recommendations in this area, based on the idea that future imams must acquire information culture. The article in the Information Society examines in detail the necessity of the efficient use of information in the field of education and makes sure that information is circulated quickly and of high quality within the education system, which becomes the primary criterion for the advancement and development of the nation. The primary determinants of the information culture creation of secondary specialized Islamic education students are elucidated. Every student and adolescent in the twenty-first century must adhere to the fundamentals of information culture; issues with its application in the classroom and, naturally, fostering a more positive Internet culture are emphasized. The scholarly essay provides an examination of research done on how students in secondary specialized educational institutions use social media and the Internet. The development of students' information cultures in secondary specialized Islamic educational institutes has not been researched at all; this is a scientific study conducted in Uzbekistan as well as all of Central Asia. Information culture of students studying in secondary specialized Islamic educational colleges has been thoroughly defined and formed into formation standards